PENINGKATAN PEMAHAMAN FIKIH KONTEMPORER MELALUI MODEL PROBLEM BASED LEARNING PADA MAHASISWA AHWAL ASY-SYAKSIYYAH SEMESTER 4 DI STAI DARUSSALAM LAMPUNG: PENINGKATAN PEMAHAMAN FIKIH KONTEMPORER MELALUI MODEL PROBLEM BASED LEARNING PADA MAHASISWA AHWAL ASY-SYAKSIYYAH SEMESTER 4 DI STAI DARUSSALAM LAMPUNG - Fitriyah; Nur Indah Sari; Siti Kholijah (LPPM STAI Darussalam Lampung, 2023)
This research is motivated by the low understanding of contemporary fiqh due to the discussion method used in learning. Where there were only a few students who played an active role, the rest were just silent and listened. This study aims to increase students' understanding of STAI Darussalam Lampung in Contemporary Jurisprudence Courses through problem-based learning models. The method in this study used the classroom action research (PTK) method by adopting the Kurt Lewin model using 4 stages, namely planning, action, observation and reflection. The subjects in this study were 4th and 6th semester students majoring in ahwal asy-syaksiyyah. The results of this study are that there is a significant increase in the ability to understand theory and students are able to think critically and thoroughly.